Multicultural Islamic Education Evaluation Through the Lens of Inclusive Pedagogy and Ethical Humanism - Nafis, Ahmad; Asy Syauqi, Faris; Astuti, Tri (Universitas Muhammadiyah Surakarta, 2026)
Contemporary multicultural Islamic education faces a significant challenge in aligning its educational evaluation practices with the broader objectives of inclusivity, ethical humanism, and intercultural coexistence. Existing evaluation systems remain predominantly oriented toward cognitive achievement, standardized assessment, and behavioral compliance, thereby inadequately capturing ethical awareness, empathy, social responsibility, and intercultural competence within diverse educational settings. This study aims to develop a transformative evaluation framework for multicultural Islamic education through the lens of inclusive pedagogy and ethical humanism. Employing a qualitative-dominant mixed-methods design with an exploratory sequential approach, the research was conducted across four Islamic educational institutions in Malang, Indonesia. The participants consisted of 36 educational stakeholders, including Islamic education lecturers, teachers, educational evaluators, administrators, and postgraduate students. Data were collected through semi-structured interviews, document analysis, and expert validation questionnaires, and subsequently analyzed using thematic analysis and descriptive statistical techniques. The findings reveal that current evaluation practices within multicultural Islamic education remain heavily dominated by cognitive-oriented paradigms, resulting in the marginalization of ethical, intercultural, and humanistic dimensions of learning. The study identifies six core evaluative dimensions essential for transformative multicultural Islamic education, namely inclusive participation, intercultural competence, ethical awareness, empathy and social sensitivity, collaborative engagement, and equitable assessment practices. These dimensions were integrated into a proposed evaluation framework grounded in inclusive pedagogy and ethical humanism. The study contributes theoretically by reconstructing educational evaluation beyond academic performance and offers practical implications for curriculum reform, teacher development, inclusive educational policy, and sustainable human-centered education within pluralistic societies.